2016
DOI: 10.5114/jcb.2016.64441
|View full text |Cite
|
Sign up to set email alerts
|

Salvage high-dose-rate brachytherapy for histologically confirmed macroscopic local relapsed prostate cancer after radical prostatectomy

Abstract: PurposeTo evaluate the feasibility of the use of real-time magnetic resonance imaging (MRI)-transrectal ultrasound (TRUS) fusion guided high-dose-rate brachytherapy (HDR-BT) +/– external beam radiation therapy (EBRT) in patients with histologically-proven local relapse after radical prostatectomy.Material and methodsWe retrospectively reviewed 13 patients treated with real-time MRI-TRUS fusion HDR-BT for a local relapse of prostate cancer after radical surgery. All patients underwent multiparametric magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(45 reference statements)
1
9
0
2
Order By: Relevance
“… 42 This study reported a favorable rate of biochemical remission in patients who did not receive ADT despite otherwise unfavorable baseline characteristics such as a mean presalvage PSA of 2.3 ng/mL. These results are somewhat more favorable than older, small, retrospective series reporting on the efficacy of focal brachytherapy in the salvage setting 43 , 44 likely owing to the sensitivity of positron emission tomography to detect local recurrences earlier in their natural history in the contemporary reports.…”
Section: Discussionmentioning
confidence: 72%
“… 42 This study reported a favorable rate of biochemical remission in patients who did not receive ADT despite otherwise unfavorable baseline characteristics such as a mean presalvage PSA of 2.3 ng/mL. These results are somewhat more favorable than older, small, retrospective series reporting on the efficacy of focal brachytherapy in the salvage setting 43 , 44 likely owing to the sensitivity of positron emission tomography to detect local recurrences earlier in their natural history in the contemporary reports.…”
Section: Discussionmentioning
confidence: 72%
“…Buchser et al reported 11 patients who received salvage HDR-BT (15 Gy/1 fraction) with EBRT (37.5 Gy/15 fractions) for histologically confirmed, locally relapsed macroscopic prostate cancer after radical prostatectomy with a median volume of 3.34 cc (range: 1.98–6.76 cc). 17 At a median follow-up of 7 months, all patients showed an appropriate biochemical response, and the acute GU/gastrointestinal toxicity levels were acceptable; there were no cases of late toxicity.…”
Section: Discussionmentioning
confidence: 78%
“…Unfortunately, no such restrictions are available for salvage HDR-BT [ 11 ]. As an accurate spatial dose delivery in salvage treatments is essential, many clinical groups prefer HDR-BT for treatment delivery [ 22 ]. 125 I seeds have the tendency to migrate from their original position and this phenomenon may have a negative effect on the intended dose delivery to the GTV.…”
Section: Discussionmentioning
confidence: 99%